The Progressive Development and Codification of Peremptory Norms of International Law - Keinänen, Sami (Helsingin yliopisto, 2021)
Abstract Faculty: Faculty of Law Degree programme: Master of Laws Study track: International Law Author: Sami Keinänen Title: The Progressive Development and Codification of Peremptory Norms of International Law Level: Master’s Thesis Month and year: November 2021 Number of pages: XXXII + 80 Keywords: International Law, Human Rights Law, Jus Cogens, Peremptory Norm, State Immunity, State Responsibility, Universal Jurisdiction, Draft Conclusions on Peremptory Norms of International Law, International Law Commission Supervisor or supervisors: Ukri Soirila Where deposited: University of Helsinki Library Additional information: Abstract: Jus cogens has attributes from both legal positivism and natural law and has witnessed narrow and more expansive interpretations. This thesis examines the case law related to peremptory norms, the theoretical and practical features, defects and definitional issues of jus cogens, and the ideological changes which need to take place in order to facilitate its future applications as a general rule of international law. Article 53 of the Vienna Convention defines peremptory norms as rules accepted and recognized by the international community of states as a whole as norms from which no derogation is permitted, voiding treaties if at the time of their conclusion they conflict with peremptory norms of international law, effectuating a normative hierarchy of international law and allowing sovereign states to be bound by norms which they have not explicitly consented to. The essential nature of peremptory norms is believed to be that they reflect and protect the fundamental values of the international community. The determination of the substance and applicability of peremptory norms has been the subject of enduring debate and uncertainty. Jus cogens suggests a non-consent-based hierarchy of norms, but in its sectoral aspects its influence has been negligible due to both political and ideological reasons and the distinction between substantive and procedural rules. The international ...